Journal of Japanese Linguistics (De Gruyter Mouton, 1972)
The Journal of Japanese Linguistics focuses on important issues in the field of Japanese linguistics and language education as well as overarching objectives that shape the study of Japanese linguistics. The journal publishes articles and book reviews in the traditional subdisciplines of linguistics as well as in neighboring disciplines and promotes the exchange of knowledge regarding language education among researchers.